Impact of Organizational Culture on Risk Management Effectiveness in Multinational Corporations in India - Desai, Kavita (International Journal of Modern Risk Management, 2025)
Purpose: To aim of the study was to analyze the impact of organizational culture on risk management effectiveness in multinational corporations in India Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Organizational culture plays a key role in risk management effectiveness in MNCs in India. A strong, adaptive culture promotes proactive risk identification and effective mitigation. Open communication and leadership commitment improve decision-making. However, cultural diversity within MNCs can challenge uniform risk management, requiring tailored approaches. Unique Contribution to Theory, Practice and Policy: Competing values framework (CVF), organizational culture theory & risk culture framework may be used to anchor future studies on the impact of organizational culture on risk management effectiveness in multinational corporations in India. For multinational corporations, fostering an adaptive and involved organizational culture is critical to enhancing risk management effectiveness. From a policy perspective, MNCs should align their risk management policies with their organizational culture, as culture significantly influences how risk management strategies are executed across global subsidiaries.